THE RELATIONSHIP BETWEEN SUBJECTIVE EVALUATION AND PEJORATION IN LINGUISTICS - Zaripova Matluba Qulfitdinovna (The Conference Hub, 2025)
Pejoration, also known as derogation, is a linguistic process in which a word or expression acquires a more negative meaning over time. This semantic shift often reflects speakers’ subjective evaluations of social, cultural, or moral concepts. Subjective evaluation, in this context, refers to the attitudes, judgments, and emotional responses that language users attach to words. This paper explores the intricate relationship between subjective evaluation and pejoration, examining how social perception, cultural norms, and individual attitudes influence the semantic deterioration of lexical items. Understanding this relationship provides insights into language change, pragmatics, and the social functions of communication.
Keywords: pejoration, subjective evaluation, semantic change, pragmatics, language evolution, connotation.